Caring for Military Veterans in the Community: An Interprofessional Approach. Issue 2 (3rd April 2019) - Crytzer, Michele L.
ABSTRACT: Military veterans are at higher risk for poor health outcomes due to the myriad of physical and mental health problems that may occur during or after deployment to one or more military combat operations. To improve health outcomes for this vulnerable population, it is essential that healthcare providers employ an interprofessional approach when providing care. With increased numbers of veterans receiving healthcare in the civilian sector, community health nurses are in a unique position to implement and manage effective interprofessional collaboration that will ensure the provision of high-quality healthcare.